Influence of wastewater treatment plants' operational conditions on activated sludge microbiological and morphological characteristics. Issue 2 (17th January 2016) - Amanatidou, Elisavet; Samiotis, Georgios; Trikoilidou, Eleni; Tzelios, Dimitrios; Michailidis, Avraam
Abstract : The effect of wastewater composition and operating conditions in activated sludge (AS) microbiological and morphological characteristics was studied in three AS wastewater treatment plants (WWTPs): (a) a high organic load slaughterhouse AS WWTP, operating at complete solids retention, monitored from its start-up and for 425 days; (b) a seasonally operational, low nitrogen load fruit canning industry AS WWTP, operating at complete solids retention, monitored from its start-up and until the end of the season (87 days); (c) a municipal AS WWTP, treating wastewater from a semi-combined sewer system, monitored during the transitions from dry to rainy and again to dry periods of operation. The sludge microbiological and morphological characteristics were correlated to nutrients' availability, solids retention time, hydraulic retention time, dissolved oxygen, mixed liquor suspended solids (MLVSS), organic load (F/M) and substrate utilization rate. The AS WWTPs' operation was distinguished in periods based on biomass growth phase, characterized by different biological and morphological characteristics and on operational conditions. An anoxic/aerobic selector minimizes the readily biodegradable compounds in influent, inhibiting filamentous growth. Plant performance controlling is presented in a logic flowchart in which operational parameters are linked to microbial manipulation, resulting in a useful tool for researchers and engineers.